Pengoptimalisasian Teknik Loby dan Negosiasi Dikalangan Gen Z - Irawan, Novida; Subiakto, Vania Utamie; Hidayati, Syerli (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
The development of digital literacy has brought information closer to everyday life, creating an urgent need for educational efforts, especially among Generation Z students at PKBM Tanda Genap. This Community Service activity aims to optimize lobbying and negotiation techniques among Generation Z students, especially at PKBM Tanda Genap. These skills have become crucial components in effective communication. In today's competitive era, students are required to express opinions clearly, resolve conflicts, and reach effective agreements. Through this activity, it is hoped that Generation Z students will be better prepared to enter various professional fields such as business, public relations, politics, government, and other strategic sectors that require strong lobbying skills. Therefore, appropriate methods and techniques in lobbying and negotiation are needed to implement strategic actions and influence others effectively in educational and professional contexts. Based on this need, the author will implement a community service program entitled "Optimizing Lobbying and Negotiation Techniques Among PKBM Tanda Genap Students." The results of this program are an increase in students' understanding and practical skills in applying lobbying and negotiation techniques. As a result, students will become more confident, able to articulate their opinions, resolve conflicts, and reach effective agreements